Monte Iato, Italien: Die hellenistisch-römischen Metallfunde - Rasbach, Gabriele (e-Forschungsberichte des DAI, 2023)
The Monte Iato was settled since the 6th century BC till the 13th century AD. It is a long-term project of the University Zürich and the University Innsbruck which deals with metal finds of Hellenistic and Roman times. Sensational are the number of brooches. Most of the fibulae are of Jezerine, Alesia and Aucissa types from late 2nd and 1st century BC. Especially the Jezerine type was – at the current state of research – mainly distributed in the Italia Padana and in the north-eastern Alps. These finds might reflect auxiliar troops of the civil war.